Students' responses toward the implementation of PowToon in EFL classroom at a remote area / Heti Susanti - -, Heti Susanti (Universiti Teknologi MARA, 2022)
The development of technology in this contemporary world was undoubtedly able to support the teaching-learning process. Meanwhile, various types of applications are being used as media. For instance, PowToon. PowToon is categorized as an audiovisual presentation that provides alternative animation, picture, sound, voice, and music. PowToon videos have been used all over the world. However, this would be different for students in remote areas who are hardly taught using technology. This study revealed students' responses in a small area towards implementing PowToon in the EFL Classroom. Regarding this research, the case study was used as a research design. In collecting the data, both semi-structured interviews and close-ended questionnaires were applied. The result showed students' responses on implementing PowToon in the EFL classroom were: First, PowToon could assist students in learning English. Second, PowToon was an exciting application or media in learning, and the last PowToon increased students' creativity and motivation in learning English as Foreign Language.